Medusa and Matisse: Myth and Art in A.S. Byatt’s “Medusa’s Ankles” - Asya Sakine Uçar (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
In “Medusa’s Ankles”, English novelist and writer A.S. Byatt syncretizes a marginal female mythical figure, Medusa from Greek mythology, with a modern work of art by the French artist Henri Matisse, Pink Nude (1935). In the story, the protagonist Susannah’s visit to a hairdresser upon seeing an image of that painting culminates in an act of smashing the salon mirror. Such Medusean rage becomes symbolic as it represents a disengagement from dominant ideologies and stereotypical notions concerning a woman’s body, gender and sexuality. Extremely conscious of her aging body, classics professor Susannah interiorizes the cultural demand that women be young and beautiful; hence the fragments of the mirror reflecting distorted images point to the whole concept of ill or misrepresented women in society. Employing myth and art as key intertextual elements, Byatt presents confounding models to interpret Susannah’s struggle for identity offering innovative perspectives on body/mind dilemma and mirror/gaze argument. While the mythopoeia of Medusa, generally associated with fear and rage, could also connote creative energy and empowerment, the unusual and unattractive depiction of a female body represented by Matisse’s Pink Nude could offer a novel way of exploring the representation of women against sexually charged images in a society defined by certain assumptions.